Mapping the dark matter halo of early-type galaxy NGC 2974 through orbit-based models with combined stellar and cold gas kinematics. Issue 3 (26th November 2019) - Yang, Meng; Zhu, Ling; Weijmans, Anne-Marie; van de Ven, Glenn; Boardman, Nicholas; Morganti, Raffaella; Oosterloo, Tom
ABSTRACT: We present an orbit-based method of combining stellar and cold gas kinematics to constrain the dark matter profile of early-type galaxies. We apply this method to early-type galaxy NGC 2974, using Pan-STARRS imaging and SAURON stellar kinematics to model the stellar orbits, and introducing H i kinematics from VLA observation as a tracer of the gravitational potential. The introduction of the cold gas kinematics shows a significant effect on the confidence limits of especially the dark halo properties: we exclude more than 95 per cent of models within the 1σ confidence level of Schwarzschild modelling with only stellar kinematics, and reduce the relative uncertainty of the dark matter fraction significantly to 10 per cent within 5 R e . Adopting a generalized Navarro–Frenk–White (NFW) dark matter profile, we measure a shallow cuspy inner slope of 0.6^+0.2_-0.3 when including the cold gas kinematics in our model. We cannot constrain the inner slope with the stellar kinematics alone.